THE EFFECT OF CORPORATE IMAGE AND TRUST ON CUSTOMER LOYALTY WITHCUSTOMER SATISFACTION AS AN INTERVENING VARIABLE(Study at the Indonesian Sharia Bank, Mojokerto Branch Office, Gajah Mada) - Salma Nasywa Mufayidah; Fani Firmansyah (Adisam Publisher, 2025)
This study aims to determine the effect of corporate image and trust on customer loyalty mediated by customer satisfaction conducted at Bank Syariah Indonesia KCP Mojokerto Gajah Mada. Data collection was carried out by distributing questionnaires to 140 respondents selected using non-probability sampling techniques. Data were analyzed using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method with the help of SmartPLS software. The results of the study indicate that corporate image does not have a significant effect on customer loyalty, while trust has a significant effect on customer loyalty, and customer satisfaction is proven to have a significant effect on customer loyalty. In the mediation relationship, customer satisfaction does not mediate the relationship between corporate image and customer loyalty, but customer satisfaction is able to mediate the relationship between trust and customer loyalty. The study This felt important For done more continue so that Islamic banks especially Bank Syariah Indonesia can do the right action For maintain loyalty its customers.